PENGARUH RASIO TEPUNG BERAS MERAH (Oryza Nivara L) DAN KACANG HIJAU (Phaseolus Radiatus L) PADA PRODUK SNACK BAR TERHADAP KANDUNGAN PROTEIN DAN DAYA TERIMA OLEH ANAK USIA SEKOLAH - Rahayu, Anita; Haryanto, Irwan; Ulfah, Ardhika (Journal of Holistic and Health Sciences (Jurnal Ilmu Holistik dan Kesehatan), 2019)
Background: School-age children are vulnerable to nutrient deficiencies. The proportion of school-age children with an energy deficit of 83.9%, 64.4% of energy classified as heavy (<70% AKE) and protein deficit of 17.8% are classified as severe (<70% of PPA). lack of energy and protein in children will increase the increase in learning, increased body immunity, and growth is not optimal. One effort that can be done to meet the energy and protein needs of school-age children is by providing healthy snacks that can meet the protein needs of school-age children, one of which is a snack bar, red rice, rice flour, and green beans. Objective: To analyze the acceptability and protein content of snack bars, red rice flour and green beans Method: An experimental study using a completely randomized design with one factor, namely the ratio of the ratio of red rice flour and green beans and 3 repetitions. The research consisted of making dried green beans, making snack bars, analyzing protein content using the kejdahl method, accepting tests with a preference scale test, determining the chosen formula and protein contribution to RDA in school-age children. There were 60 panelists from Karangmukti Elementary School students. Statistical analysis using Crucial Wallist Test and One Way ANOVA. Results: There was no effect of the ratio of brown rice flour and green beans to the aroma (p = 0,473), taste (p = 0.725) and texture (p = 0.335) snack bar, but there was an influence on the color of the snack bar (p = 0.004). There is an effect of the ratio of brown rice flour and green beans to the protein content of snack bars (p = 0.00). Conclusion: the difference in the ratio of red rice flour and green beans does not affect the acceptability of aroma, taste, texture and there is an effect there is a difference in the ratio of red rice flour and green beans to the protein content of snack bars. But there is an influence on the color parameters.